PENGARUH KINERJA GURU DAN PENGEMBANGAN KURIKULUM TERHADAP PRESTASI BELAJAR SISWA DI SDI AL-BADAR TULUNGAGUNG - Sholeh, Muh Ibnu; Sokip, Sokip; Syafii, Asrop; ‘Azah, Nur; Sahri, Sahri; Al Ayyubi, Ibnu Imam (Jurnal Karya Ilmiah Pendidik dan Praktisi SD&MI (JKIPP), 2024)
Abstract This research aims to investigate the influence of teacher performance and curriculum development on student learning achievement at SDI Al-Badar Tulungagung. The research method used was quantitative with a population of 21 teachers. Data was collected through an instrument in the form of a questionnaire with an assessment using a Likert scale and analyzed using linear regression and multiple regression statistical tests. The research results show that the Teacher Performance Variable significantly contributes to student learning achievement with a correlation coefficient of 0.75 and a coefficient of determination (R^2) of 0.56 (p < 0.001). The Curriculum Development variable also makes a significant contribution to student learning achievement with a correlation coefficient of 0.68 and a coefficient of determination (R^2) of 0.46 (p < 0.001). The results of the multiple regression analysis between Teacher Performance and Curriculum Development on Student Learning Achievement show that both together make a significant contribution to student learning achievement with a coefficient of determination (R^2) of 0.67 (p < 0.001). In conclusion, teacher performance and curriculum development play an important role in improving student learning achievement at SDI Al-Badar Tulungagung. Therefore, it is recommended that schools continue to pay attention to and improve the quality of teacher performance and curriculum development as an effort to improve student learning achievement on an ongoing basis